2008
DOI: 10.1186/1741-7007-6-36
|View full text |Cite
|
Sign up to set email alerts
|

Complex chloroplast RNA metabolism: just debugging the genetic programme?

Abstract: Background: The gene expression system of chloroplasts is far more complex than that of their cyanobacterial progenitor. This gain in complexity affects in particular RNA metabolism, specifically the transcription and maturation of RNA. Mature chloroplast RNA is generated by a plethora of nuclear-encoded proteins acquired or recruited during plant evolution, comprising additional RNA polymerases and sigma factors, and sequence-specific RNA maturation factors promoting RNA splicing, editing, end formation and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 101 publications
2
75
0
1
Order By: Relevance
“…It was already suggested that the PPR protein family could have evolved to correct potential deleterious mutations in organelles, but the RFL subfamily could diversify and evolve more rapidly than the rest of the PPR family to actively compensate for mitochondrial genomic deviancies. 18,68 Mitochondrial genomes are known to be highly recombinogenic in plants, resulting in a poor conservation of gene order among related species and in the creation of large number of non-conserved and often chimeric ORF. 69 Both of these resulting phenomenons could necessitate a rapid evolution of correcting factors to prevent the production of long and heterogeneous mitochondrial transcripts or to suppress the action of CMS-inducing ORFs.…”
Section: Characterized Arabidopsis Rf-like Pprs Are Involved In Mitocmentioning
confidence: 99%
“…It was already suggested that the PPR protein family could have evolved to correct potential deleterious mutations in organelles, but the RFL subfamily could diversify and evolve more rapidly than the rest of the PPR family to actively compensate for mitochondrial genomic deviancies. 18,68 Mitochondrial genomes are known to be highly recombinogenic in plants, resulting in a poor conservation of gene order among related species and in the creation of large number of non-conserved and often chimeric ORF. 69 Both of these resulting phenomenons could necessitate a rapid evolution of correcting factors to prevent the production of long and heterogeneous mitochondrial transcripts or to suppress the action of CMS-inducing ORFs.…”
Section: Characterized Arabidopsis Rf-like Pprs Are Involved In Mitocmentioning
confidence: 99%
“…The somewhat surprising complexity of chloroplast gene expression and the large number of nuclear genes involved raises the question of whether this provides a route for regulation of the plastid by the nucleus. Alternatively it has been argued that part of the complexity may have arisen in a process of constructive neutral evolution, where preexisting nucleusencoded proteins can suppress new mutations that appear in the chloroplast (Maier et al, 2008;Gray et al, 2010;Lukes et al, 2011;Barkan and Small, 2014). A typical example where this might be the case is provided by the nucleus-encoded editing factors that make specific C-to-U changes in the sequence of chloroplast mRNAs at a posttranscriptional step (Schmitz-Linneweber et al, 2005a).…”
Section: Introductionmentioning
confidence: 99%
“…Существуют предположения о том, что наличие мно-жества промоторов и σ-факторов в хлоропластах необ-ходимо для поддержания функционального состояния генетической системы хлоропластов при возникающих мутациях (Maier et al, 2008) или, что более вероятно, для обеспечения согласованной работы всего транскрип-ционного аппарата в различных условиях (Lerbs-Mache, 2011). Возможно, оба предположения о функциональном значении множественности промоторов и σ-факторов в хлоропластах отражают разные стороны процесса транс-крипции, особенности которого еще далеко не изучены.…”
Section: дицистронные и полицистронныеunclassified